The Principal's Leadership in Strengthening Character Education in the Digital Literacy Era: A Study at Vocational School - Dhanu Lukmantoro; Nunuk Hariyati; Yatim Riyanto; Sri Setyowati (IJORER : International Journal of Recent Educational Research, 2024)
Objective: 1) How is the leadership strategy of the Head in strengthening character education in the digital literacy era?; 2) How is the curriculum that contains strengthening character education in the era of digital literacy?; 3) How can the environment of strengthening character education in digital literacy be collaborated/integrated into: curriculum, learning, intra and extra coaching, culture and school environment, so that it becomes an example for school residents?; 4) How are the results and impacts of the implementation of digital literacy era character education. Method: This research is exploratory with techniques of (1) in-depth interviews, (2) participant observation, and (3) document studies. This research data validity technique uses four kinds of criteria, namely credibility, transferability, dependability and confirmability criteria. Results: The integration of character education within digital literacy at 1 Buduran Vocational School presents a holistic model encompassing curriculum, classroom learning, intra- and extracurricular activities, and school culture. This approach ensures students develop technical skills alongside positive values and ethical behavior in using digital tools. The curriculum emphasizes both technical and ethical aspects of digital literacy. Interactive and collaborative classroom methods, with character values embedded in all subjects, create an environment conducive to character development. Novelty: It presents a holistic approach that incorporates character education into all aspects of school life—curriculum, classroom learning, extracurricular activities, and school culture—ensuring pervasive character development. The study highlights the pivotal role of the principal in promoting ethical digital practices, showcasing how effective leadership can reinforce character education in the digital era.